Pengaruh Penggunaan Gadget Terhadap Perilaku Beragama Pada Siswa Sma Negeri X Pontianak - Purwanti, Dwi Surya; Istiqomah, Istiqomah (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research is motivated by the phenomenon where all behaviors seen through gadgets would be likely imitated by children. The purpose of this study was to analyze: (1) the use of gadgets in students of SMA Negeri X Pontianak. (2) Religious behavior in SMA Negeri X Pontianak students. (3) The effect of using gadgets on religious behavior in SMA Negeri X Pontianak students. This study is a quantitative study with a student population of SMAN X Pontianak. The sampling technique used refers to the Slovin formula and a sample of 60 students is obtained. Data collection techniques using interviews, observation, documentation and questionnaires. While the data analysis techniques used are instrument analysis, descriptive analysis, and causal relationship analysis. The results of data analysis show that the use of gadgets by students of SMA Negeri X Pontianak is in the high category with an average score of 92.5. Moreover, it is known that the religious behavior of the students of SMA Negeri X Pontianak is in the low category with an average score of 45.32. Finally, it is known that the contribution of gadget use to religious behavior in SMA Negeri X Pontianak students is 12.8%, while the rest is influenced by other variables outside this study.Keywords: Use of gadgets, Religious Behavior